Usage and Perception of Open Access Resources: A Study of Select Universities in Bangladesh - Monirul Islam, M.; Bhattacharya, Udayan; Khan Tonmoy, Tazbir (Journal of Information and Knowledge, 2022)
The goal of this research is to examine the current state of Open Access (OA) Resources in six private and public universities in Bangladesh. It also seeks to analyze students’ awareness, utilization of, and attitude towards OA resources. Findings: The study found that 60% of the students perceive their universities have enough OA resources whereas the other 40% think their universities do not possess enough. In the meantime, only 50% of them are frequent users while the other 30% know but never used and the rest 20% have no idea about OA resources. However, the awareness of OA Resources amongst students is increasing day by day. The students possess a positive perception of OA Resources. Methodology: The questionnaire, direct interviews, various documentaries, and direct observation are used for the present study. We applied interview and own observation methods as the questionnaire approach had few limitations while collecting the data that is why so that this method was used to collect the required information to supplement the questionnaire methods and to bring more clarity to the data. The questionnaires were distributed personally to the students. Then we tried to understand the knowledge, utilization, and attitude of OA resources. Data Collection: The major step of the study for data collecting was the survey data from selected universities of Bangladesh. Moreover, the discussions were held with the students of these universities to examine awareness, use, and perception of OA Resources. Various journals articles, online sources, like Google, blog sites, Google Scholars, etc. have been used in this research.